Histories of the Middle East studies in Middle Eastern society, economy and law in honor of A.L. Udovitch - Margariti, Roxani Eleni, 1969-; Sabra, Adam Abdelhamid, 1968-; Sijpesteijn, Petra.; Udovitch, Abraham L. (Islamic History and Civilization, 2011)
For four decades Abraham L. Udovitch has been a leading scholar of the medieval Islamic world, its economic institutions, social structures, and legal theory and practice. In pursuing his quest to understand and explain the complex phenomena that these broad rubrics entail, he has published widely, collaborated internationally with other leading scholars of the Middle East and medieval history, and most saliently for the purposes of this volume, taught several cohorts of students at Princeton University. This volume is therefore dedicated to his intellectual legacy from a uniquely revealing angle: the current work of his former students. The papers in this volume range chronologically from the period preceding the rise of Islam in Arabia to the Mamluk era, geographically from the Western Mediterranean to the Western Indian Ocean and thematically from the political negotiations of Christian and Islamic Mediterranean sovereigns to the historiography of Western Indian Ocean port cities.